Students' learning motivation and cognitive competencies in the PP and PBL models - Nurul Hidayati; Didimus Tanah Boleng; Krishna Purnawan Candra (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
The learning model is one of the critical factors in boosting student to have good learning motivation (LM) and cognitive competencies (CC). In two academic years (2016-2017), only 19.6% of Senior High School (SHS) students in Samarinda passed minimal competence in Biology subject. This research was conducted to find out a better learning model in Biology subject to replace the conventional learning (CL) model. A quasi-experiment using three learning models, i.e. Problem Posing (PP), Problem-based Learning (PBL), and CL, were conducted in all three 11th grade student classes at Public Islamic SHS (PISHS) I Samarinda in the period of odd semester of 2018/2019 academic year. The LM and CC data were collected by questionnaires, each has 40 and 9 problems, respectively.  The LM and CC data were analyzed by ANOVA and ANCOVA continued by comparison test using Bonferroni test (p< 0.05), respectively. The results showed that the CL model could increase the CC, but not improve LM. However, PP and PBL model were significantly more effective (p< 0.05) in increasing both the CC and LM. The PP is superior in improving the LM, while the PBL is superior in gaining the cognitive competence.